HUBUNGAN POWER OTOT TUNGKAI DAN KOORDINASI MATA DAN KAKI DENGAN KETEPATAN SHOOTING SEPAKBOLA PADA ATLET PUSAT PENDIDIKAN DAN LATIHAN PELAJAR (PPLP) RIAU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study was to determine the relationship between leg muscle power and eye and foot coordination with shooting accuracy for the Riau Student Education and Training Center (PPLP) players. The study was carried out in August - December 2022, with samples taken from the entire population of 18 people. Based on the results obtained, leg muscle power has a relationship with the shooting accuracy of the Riau Student Education and Training Center (PPLP) players. Eye-foot coordination has a relationship with shooting accuracy in Riau Student Education and Training Center (PPLP) players. And there is a joint relationship between leg muscle power and eye-foot coordination on shooting accuracy on the Riau Student Education and Training Center (PPLP) players.Key Words: The relationship between leg muscle power, eye and foot coordination, soccer shooting accuracy